ANALISIS FITOKIMIA ENCENG GONDOK (Eichhornia crassipes) DAN EFEKNYA SEBAGAI AGEN PHOTOREDUKSI Fe3+ - Rorong, Johnly A.; Suryanto, Edi (Sam Ratulangi University, 2010)
Eichhornia crassipes is a weeds to people. The objectives of this research were to analyze phytochemicalcontent and photoreduction activity. Phytochemical content that analyzed were total phenolic, total flavonoidand condenced tannin. Photoreduction activity were done using reduction of Fe3+ to Fe2+. The highest totalphenolic, flavonoid and condenced tannin were extracted with water in leaves, 26.327, 3.191, 25.300 mg/kgrespectively. Photoreduction activity of enceng gondok decreases Fe3+ concentration from 9,111 to 1,500 ppm.Enceng gondok posses photoreduction activity because it has phenolic, flavonoid and condenced tannincontent.